PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING DI DINAS PENDIDIKAN DAN KEBUDAYAAN KOTA LUBUKLINGGAU - Idayati, Irma; Surajiyo, Surajiyo; Hazalena, Marvia (Jurnal Media Ekonomi (JURMEK), 2020)
This study entitled The Effect of Competence and Work Environment on Employee Performance through Motivation as an Intervening Variable in the Education and Culture Office of the City of Lubuklinggau. The method used in this study using a questionnaire and observation. Testing the first hypothesis, namely Variable Competence (X1) on Motivation (Z) "shows that t count produces a coefficient of 16.347. With a sample size of 58 found df = 58 (58-2) at a significant level of 0.05, the critical value of t table is 1.672. with these results it can be said that competence has a significant effect on motivation because tcount (16.347)> t table (1.672). The second hypothesis testing is that it can be said that the work environment has a significant influence on motivation because tcount (10.038)> t table (1.672). Third Hypothesis testing can be said that competence has a significant effect on employee performance because tcount (10.412)> t table ( 1.672). The fourth hypothesis testing can be said that the work environment has a significant influence on employee performance because tcount (14.897)> t table (1.672). " and testing the fifth hypothesis, it is found that the value of fcount obtained is 152.197> F table = 3.16 and the simultaneous significant level of sig F is 0.000b. This shows that competence and work environment have a significant influence on employee performance (Y).